Estimation of reliability of air engines with use of Bayes strategy - Тамаргазін, О. А. (Proceedings of National Aviation University (archive), 1999)
Considered is the possibility of using Bayes strategy to a solution of problems of recognizing early stages of deterioration of reliability of air engines with use of constantly modified density function of main parameters of their reliability